General Self-Efficacy and Psychological Resilience Promote Skill Acquisition Rate Under Psychological Pressure. (23rd August 2017) - Crane, Monique F.; Brabazon, Gareth; Gucciardi, Daniel F.; Loveday, Thomas; Wiggins, Mark
Abstract : This study extends the limited body of research exploring the association between psychological resources and performance under pressure. It was anticipated that participants' general self-efficacy and resilience would positively influence skill acquisition rate more under high pressure, than low pressure. Eighty-one undergraduate students ( M age = 22.93; SD = 7.53; 50.6% female) participated in a learning task: to fly a flight simulator. The within-subjects variable was the participant's ability to steadily control the aircraft roll across six trials. Psychological pressure was manipulated between-subjects and general self-efficacy and resilience were measured moderator variables. Findings indicated that under high pressure, higher levels of general self-efficacy and perceived resilience predicted faster initial skill acquisition compared to those with lower levels of these resources. In contrast, in the low-pressure condition, the skill acquisition rate was the same irrespective of psychological resources. This research highlights the importance of psychological resources in pressured training contexts.